Participatory networks: the library as conversation. - Lankes RD; Silverstein J; Nicholson S (Information Technology & Libraries, 2007)
The goal of the technology brief is to familiarize library decision-makers with the opportunities and challenges of participatory networks. In order to accomplish this goal the brief is divided into four sections (excluding an overview and a detailed statement of goal): a conceptual framework for understanding and evaluating participatory networks; a discussion of key concepts and technologies in participatory networks drawn primarily from Web 2.0 and Library 2.0; a merging of the conceptual framework with the technological discussion to present a roadmap for library systems development; and a set of recommendations to foster greater discussion and action on the topic of participatory networks and, more broadly, participatory librarianship. This summary will highlight the discussions in each of these four topics. For consistency, the section numbers and titles from the full brief are used.